The Effectiveness of Digital-Based Service Innovation in The Personnel And Human Resources Development Agency Of Ciamis District - Mardiana, Gina; Triyanti Dewi, Uci; Nursetiawan, Irfan (LPPM Universitas Jambi, 2024)
As an institution responsible for government affairs in the field of personnel, the Ciamis Regency Personnel and Human Resources Development Agency realizes the importance of digitalization in services. Therefore, the Ciamis Regency Personnel and Human Resources Development Agency has launched several digital service innovations for employees in the Ciamis Regency work environment. This research uses a qualitative descriptive approach, collecting data through observation, interviews and documentation. This research aims to describe various digital service innovations available at the Civil Service and Human Resources Development Agency of Ciamis Regency. Digital services at the Civil Service and Human Resources Development Agency of Ciamis Regency are running effectively, even though Si-Bangpeci is currently in the maintenance phase due to integration with the provincial central agency. Focus on digital service innovation supports Good Governance. Collaboration between the Ciamis Regency Government and the Personnel and Human Resources Development Agency has produced digital service innovations that increase the efficiency of personnel services, but implementation and integrity challenges still need to be overcome to ensure optimal service provision.